Contact sport participation predicts instrumental aggression, not hostile aggression, within competition: quasi-experimental evidence. Issue 1 (9th January 2017) - Sherrill, Andrew M.; Bradel, Lauren T.
Abstract : Purpose: Findings are mixed with regard to the link between contact sport participation and aggression. One possibility is that contact sport participation may be associated with instrumental aggression but not hostile aggression. The purpose of this paper is to employ a quasi-experimental design to investigate the prediction that young men who regularly participated in contact sports during high school, compared to those who did not, exhibit a greater disposition toward aggression in response to a non-provoking situation (instrumental aggression) and no dispositional difference in response to a provoking situation (hostile aggression). Design/methodology/approach: The Taylor Aggression Paradigm was used to manipulate three levels of provocation (no provocation, low provocation, high provocation) and observe aggressive behavior in participants who varied in contact sport participants (yes, no). Findings: Results indicated a significant two-way interaction between provocation level and contact sport participation such that contact sport participation positively predicted aggression before provocation was initiated (instrumental aggression), not after (hostile aggression). Originality/value: This is one of only a limited number of studies to examine the link between contact sport participation and aggression at varying levels of provocation. Findings suggest the form of aggression associated with contact sport participation is predominately instrumental.